2019
DOI: 10.1177/1038416219843628
|View full text |Cite
|
Sign up to set email alerts
|

Fieldwork placement outcomes for international higher education students: A systematic literature review

Abstract: Fieldwork experiences can be particularly challenging for international, higher education students, as they face language and cultural difficulties, which can affect their academic progress and their fieldwork interactions with supervisors and clients. This review synthesised findings from 27 studies referring to higher education courses that employed fieldwork placements. The aims were to examine the effectiveness of placement support programs and to collate strategies that international students and/or place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“… Literature review Australia International students Migrants 6 articles (other literature related to other student groups who face barriers in nursing education was also included) Databases (CINAHL, PubMed, Academic Search Complete, Medline, Education Search Complete, Health Source: Nursing/Academic Edition, Science Direct, Scopus, Google Scholar) and reference lists of potentially relevant studies Bachelor Clinical 105 Kraenzle Schneider (2019) [ 148 ] To discuss the challenges of international doctoral nursing students and recommend strategies to support them. Literature review United States International students 17 articles Databases (CINAHL, Medline, PsychInfo, PubMed, Scopus) and ‘other search methods’ Graduate (Doctorate) 106 Lee (2019) [ 149 ] To examine the effectiveness of programs to improve (clinical) placement outcomes of international students and to collate recommendations made by international students and/or placement supervisors that they felt might improve placement outcomes. Systematic review Australia International students 10 articles (other literature related to other disciplines was also included) Databases (PsychInfo, CINAHL Plus, ProQuest Central, ERIC, Informit A+ Education, Informit MAIS) and reference lists of included articles Bachelor Graduate (Masters) Clinical 107 Malecha (2012) [ 17 ] To identify and summarize what have been reported as stressors to foreign-born nursing students living and studying in the United States.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Literature review Australia International students Migrants 6 articles (other literature related to other student groups who face barriers in nursing education was also included) Databases (CINAHL, PubMed, Academic Search Complete, Medline, Education Search Complete, Health Source: Nursing/Academic Edition, Science Direct, Scopus, Google Scholar) and reference lists of potentially relevant studies Bachelor Clinical 105 Kraenzle Schneider (2019) [ 148 ] To discuss the challenges of international doctoral nursing students and recommend strategies to support them. Literature review United States International students 17 articles Databases (CINAHL, Medline, PsychInfo, PubMed, Scopus) and ‘other search methods’ Graduate (Doctorate) 106 Lee (2019) [ 149 ] To examine the effectiveness of programs to improve (clinical) placement outcomes of international students and to collate recommendations made by international students and/or placement supervisors that they felt might improve placement outcomes. Systematic review Australia International students 10 articles (other literature related to other disciplines was also included) Databases (PsychInfo, CINAHL Plus, ProQuest Central, ERIC, Informit A+ Education, Informit MAIS) and reference lists of included articles Bachelor Graduate (Masters) Clinical 107 Malecha (2012) [ 17 ] To identify and summarize what have been reported as stressors to foreign-born nursing students living and studying in the United States.…”
Section: Resultsmentioning
confidence: 99%
“…Equally noted was the importance of promoting diversity and fostering a sense of belonging [ 17 , 37 , 108 , 127 , 145 , 146 , 148 , 151 154 ]. It was also recommended that educators and preceptors receive training to ensure that they are aware of the challenges that many foreign-born students encounter and to provide them strategies and tools for teaching a multi-lingual and culturally diverse student population [ 17 , 18 , 33 , 34 , 37 , 50 , 60 , 63 65 , 68 , 71 , 73 85 , 87 89 , 91 – 96 , 103 , 106 – 108 , 111 113 , 115 , 117 , 120 , 121 , 123 , 125 128 , 131 , 138 , 139 , 141 , 143 , 145 147 , 149 154 ]. It was also suggested that instructors have smaller classes, clinical groups and student-supervisory ratios, and more time allotted to devote to foreign-born students [ 20 , 50 , 51 , 64 , 65 , 74 , 79 , 104 , 108 , 112 , 120 , 121 , 127 , 129 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintaining their culture and values, but also accepting and being open to differences, were identi ed as coping mechanisms to deal with cultural barriers, while positive thinking and celebrating successes, were highlighted as ways that students boost their sense of self-worth and reduce stress (20,34,45,53,60,62,68,69,74,78,80,82,85,96,112,116,134,(144)(145)(146). Numerous papers also reported that students use various strategies (e.g., asking for clari cations, using non-verbal communication, doing additional reading), and actively develop their skills, in order to gain con dence and overcome language and academic barriers (18,20,50 There were several interventions that were described or suggested in the literature as being potentially helpful to foreign-born students (reported in (20,39,40,53,54,63,68,93,97,101,109,110,116,118,128,138,(141)(142)(143)145).…”
Section: Location Educational Context and Populationmentioning
confidence: 99%